Mechanism and regulation of ribosomal RNA transcription - Gogain, Joseph Carey, author; Paule, Marvin, advisor (Colorado State University. Libraries, 2003)
The sole responsibility of RNA polymerase I (pol I) is the transcription of the ribosomal RNA (rRNA) genes. This transcription can account for up to 60% of the total cellular RNA that is being transcribed in an actively dividing cell. Due to the large amounts of energy this transcription requires, it is of utmost importance for the cell to be able to regulate rRNA transcription efficiently. The rate at which pol I transcribes rRNA, closely follows cellular growth rate. Any change in cell proliferation results in immediate down regulation of rRNA transcription. The mechanisms responsible for mediating this rapid change in transcription rate are not completely understood. In order to fully comprehend the process by which rRNA is being regulated, it is important to characterize the functions of each of the pol I transcriptional components. The work presented herein focuses on identifying the important interactions involved in transcription factor binding, to both other factors within the pol I transcriptional machinery, and to the rRNA promoter. We report here the institution of a reconstituted transcription system for Saccharomyces cerevisiae, and the initial characterization of transcription factor DNA-binding activities using electrophoretic mobility shift and photo-cross-linking assays. Furthermore, we identify an interaction between a pol I specific subunit and a subunit of the fundamental pol I transcription factor. An interaction that may be important for the recruitment of pol I to the rRNA promoter. Additionally, we report the identification of the Acanthamoeba castellanii homologue to the yeast pol I transcription factor Rrn3p. We have characterized the activity of this factor, TIF-IA, in the A. castellanii system and show that it is required for the recruitment of pol I to the rRNA promoter.
Keywords: biochemistry; microbiology; molecular biology